PENGARUH PESAN KAMPANYE #KERENTANPANYAMPAH THE BODY SHOP INDONESIA TERHADAP SIKAP KHALAYAK : SURVEI PADA FOLLOWERS AKUN INSTAGRAM @THEBODYSHOPINDO.IMPACT - Denisa Nur Wahidah, (2022)
The existence of waste that continues to increase every year makes the environment more polluted. One of the causes of the accumulation of waste is the use of plastic which is still very widely used. Based on this, The Body Shop Indonesia is trying to overcome this by strengthening its commitment to environmental issues, especially the issue of plastic pollution by launching the #KerenTanpaNyampah campaign. The Body Shop Indonesia uses social media Instagram as a medium for spreading campaign messages. This study aims to determine the influence of The Body Shop Indonesia's #KerenTanpaNyampah campaign message on public attitudes. The theory used is attribution theory. The survey method was used by researchers to distribute questionnaires to 100 respondents following the Instagram account @thebodyshopindo.impact by using a purposive sampling technique. In the coefficient of determination test, it was found that the influence of the independen variable (Campaign Message) on the dependent variable (Audience Attitude) was 56.1% and the remaining 43.9% was determined by other factors. In the t test, it was found that the t arithmetic value was 11.190 > t table 1.984 and from the sig value 0.000 < 0.025, it can be concluded that Ho is rejected and Ha is accepted. It can be interpreted that there is an influence of The Body Shop Indonesia's #KerenTanpaNyampah campaign message on public attitudes.